2016
DOI: 10.1002/pc.23937
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma treatment on mechanical and thermal properties of marble powder/epoxy composites

Abstract: The aim of this work was to study the effect of the plasma treatment on the behavior of composite structures reinforced with marble powder, obtained as processing waste in the “Custonaci” basin. Moreover, different filler amounts (i.e., 10%wt, 20%, 30% in weight) were investigated. For the mechanical characterization, tensile and flexural quasi‐static tests, Charpy impact test, and dynamic mechanical thermal analysis (DMTA) were performed. For the thermal stability, thermogravimetric analysis was carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…The void volume content of all the composite samples did not exceed 2%, which indicates good quality and lack of porosities [31,33]. The lowest value was denoted for the PLA-LC-4.6 sample and the highest for the PLA-LC-39.8 one.…”
Section: Resultsmentioning
confidence: 99%
“…The void volume content of all the composite samples did not exceed 2%, which indicates good quality and lack of porosities [31,33]. The lowest value was denoted for the PLA-LC-4.6 sample and the highest for the PLA-LC-39.8 one.…”
Section: Resultsmentioning
confidence: 99%
“…The storage modulus was increased, and the damping factor peak shifted toward the higher temperature with the addition of quartz content in epoxy material. Fiore et al explored the impact of plasma treated as well as untreated marble dust as reinforcement in the epoxy composite for the analysis of dynamic mechanical properties. The results shown that glass‐transition temperature for untreated marble dust‐filled composite was decreased by 5°C from the neat epoxy about 65°C while the treated marble dust was increased by about 5°C.…”
Section: Introductionmentioning
confidence: 99%
“…Results of thermogravimetric analysis for: (a) resin composites and (b) dental composites. 79 after comparison with neat HDPE it was found that HDPE decomposes at 423 C while cenospherereinforced HDPE decomposed at 483 C thus providing better stability. 90 Post curing thermal stability for FA-reinforced cotton fabric composite was examined and it was revealed that FA with portland cement is the most stabilized composite reinforcement than pure cotton fabric.…”
Section: Effect Of Fly Ash Reinforcement On Thermal Behaviormentioning
confidence: 97%